In Silico and In Vitro Study of Janus Kinases Inhibitors from Naphthoquinones - Kamonpan Sanachai; Panupong Mahalapbutr; Lueacha Tabtimmai; Supaphorn Seetaha; Nantawat Kaekratoke; Supakarn Chamni; Syed Sikander Azam; Kiattawee Choowongkomon; Thanyada Rungrotmongkol (Molecules, 2023)
Janus kinases (JAKs) are involved in numerous cellular signaling processes related to immune cell functions. JAK2 and JAK3 are associated with the pathogenesis of leukemia and common lymphoid-derived illnesses. JAK2/3 inhibitors could reduce the risk of various diseases by targeting this pathway. Herein, the naphthoquinones were experimentally and theoretically investigated to identify novel JAK2/3 inhibitors. Napabucasin and 2′-methyl napabucasin exhibited potent cell growth inhibition in TF1 (IC50 = 9.57 and 18.10 μM) and HEL (IC50 = 3.31 and 6.65 μM) erythroleukemia cell lines, and they significantly inhibited JAK2/3 kinase activity (in a nanomolar range) better than the known JAK inhibitor, tofacitinib. Flow cytometric analysis revealed that these two compounds induced apoptosis in TF1 cells in a time and dose-dependent manner. From the molecular dynamics study, both compounds formed hydrogen bonds with Y931 and L932 residues and hydrophobically contacted with the conserved hinge region, G loop, and catalytic loop of the JAK2. Our obtained results suggested that napabucasin and its methylated analog were potential candidates for further development of novel anticancer drug targeting JAKs.